БЕРДАҚ ШЕЪРИЯТИ ЯНГИ ТАРЖИМАЛАРДА - Қурамбоева, Г. (SCIENCE and SOCIETY, 2022)
The article deals with the translator’s mastery in transmitting the poetic spirit, national character of the original work, the correspondence between the forms and content, as well as some achievements and shortcomings in translations of the Berdakh’s poetry into the Uzbek language.